Evaluation of trends of drug-prescribing patterns based on WHO prescribing indicators at outpatient departments of four hospitals in southern Ethiopia - Summoro TS; Gidebo KD; Kanche ZZ; Woticha EW (Dove Medical Press, 2015)
Temesgen Sidamo Summoro,1 Kassa Daka Gidebo,2 Zewde Zemma Kanche,1 Eskinder Wolka Woticha2 1School of Medicine, College of Health Sciences and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2School of Public Health, College of Health Sciences and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia Background: Rational prescribing is a primary step to ensure rational drug use. Often, half of the medicines are prescribed irrationally and half of these are even used incorrectly as the patients fail to take their medicines appropriately. The aim of this research was to evaluate drug-prescribing patterns of four hospitals in southern Ethiopia.Methods: A retrospective cross-sectional study was conducted between May 15 and June 25, 2014, to evaluate the drug-prescribing patterns based on the World health Organization (WHO) prescribing indicators. The prescription papers, kept for the last 1 year in the outpatient departments of the four hospitals, were analyzed according to WHO guidelines. Also, prescriptions in the hospitals were analyzed to determine the most frequently prescribed drugs. All the statistical calculations were performed using SPSS® version 20.0 software.Results and discussion: The average number of drugs per prescription ranges from 1.82±0.90 to 2.28±0.90, whereas the percentage of use of antibiotics and injections ranged from 46.7 to 85 and 15 to 61.7, respectively. The average percentages of drugs prescribed by generic name and from the essential drugs list were 95.8 and 94.1, respectively. Anti-infective and analgesic drugs are found to be the most frequently prescribed medicines. In terms of polypharmacy, there was a slight deviation in prescribing patterns from what is acceptable according to the WHO criteria. Prescribing by generic name and from essential drug list was almost optimal. There was a significant deviation in the use of injectables in two of the four hospitals (50%), whereas their use in the other two hospitals was within the acceptable range. The use of antibiotics in all the hospitals in present study was higher than the acceptable range.Conclusion: Generally, it seems that there is need for improvement of the prescribing patterns in the hospitals, although this should be consolidated with further studies to link the patient diagnosis and the prescribed medications. Keywords: prescribing indicators, medicines, hospitals, rational prescribing, Ethiopia